المجالس المنتخبة كأداة للتنمية المحلية - سرير عبد الله, رابح (revue mofakir, 2018)
الملخص : الإنسان طاقة يمسكها أو يستعملها حسب أقوى حاجاته وسلوك قادته معه، والمجالس المنتخبة تمتلك طاقة الناخبين وتوظف تلك الطاقة على مدى قدرة المثلين المحلين في التعبير عن رغبات المواطنين، ومدى إخلاص المنتخبين لناخبيهم وهذه العلاقة الجدلية بين الناخب من جهة والمنتخب وما يقدمه من خدمات وتنمية محلية من جهة ثانية هي التي تحقق الكفاية الذاتية من خلال خلق آليات للمشاركة المجتمعية وآليات للرشادة في التسيير، حيث أن العمل بمبادئ الحكم الراشد يوفر المال، ويرشد النفقات ويحل المشكلات المحلية بكل أصنافها ومنه تحقيق الكفاية المحلية وهو المطلوب. وبالمقابل من ذلك فإن أي تهميش للمواطن معناه تهميش القدرات المحلية مما يجعل الجماعات المحلية في دائرة مفرغة لا تستفيد من الطاقات المتوفرة من جهة ولا تحقق الكفاية الذاتية التي تشكل العمود الفقري للتنمية والتطور المحلي والبحث الذي هو أمامنا حاول أن يفسر القوة الكامنة بين الوسائل المادية والبشرية على المستوى المحلي وصولا إلى تحقيق الرشادة في التسيير المحلي بالاعتماد على النفس وتحقيق الكفاية الذاتية.   Abstract Maintained by human power or used by the most powerful needs and behavior led him The elected councils have the power of voters and employ that energy capacity doubled over the shops in the expression of the wishes of citizens, and elected to the sincerity of their constituents and the contentious relationship between the voter on the one hand. And the team and its services and local development on the other hand is achieved self-sufficiency through the creation of mechanisms for community participation and mechanisms for Rashadp in management , where the work to the principles of good governance, saves money , and guides the expenditures and solve local problems of all kinds and from the achievement of sufficiently local , which is required. On the other hand that any marginalization of the citizen means the marginalization of local capacity , making local communities in a vicious circle not take advantage of the capabilities available on the one hand it would not achieve self-sufficiency , which form the backbone of development and development of local research that is we have tried to explain the underlying strength of the material means and human The local level so as to achieve rationality in local governance through self-reliance and to achieve self-sufficiency.